L’INFLUENCE DE L’ELECTROSTIMULATION SUR LES TRANSFORMATIONS POST-MORTEM DES RESERVES ENERGETIQUES DU MUSCLE DE BŒUF - Felicia Dima; Camelia Vizireanu (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The experimental results show that electrical stimulation has a positive effect on the biochemical changes and technological properties of beef meat. Given the beneficial changes reported in the literature, we used a portable device for electrical stimulation of the beef carcasses that can be used in small size slaughterhouses.